RUNX1::MECOM rearrangement in myeloid neoplasm post cytotoxic therapy following sarcoma treatment: a case presentation and review of the literature - Miriam Sandnes; Øystein Sefland; Irini Ktoridou-Valen; Rakel Brendsdal Forthun; Hilde Kollsete Gjelberg; Lars Henrik Dahl Hamnvik; Håkon Reikvam; Tor Henrik Andersson Tvedt (Hematology)
Objectives Myeloid neoplasms occurring after cytotoxic therapy (MN-pCT), previously termed therapy-related myelodysplastic neoplasia (MDS) or therapy-related acute myelogenous leukemia (AML), pose significant treatment challenges due to high resistance, poor chemotherapy tolerance, and relapse.Methods We present a 73-year-old woman with therapy-related AML following treatment for myxofibrosarcoma, characterized by the rare RUNX1::MECOM fusion resulting from a t(3;21)(q26;q22) chromosomal translocation. We also review the current literature regarding cases of this rare translocation.Results The patient, previously treated with chemotherapy and radiotherapy for sarcoma, was diagnosed with pancytopenia and hypoplastic bone marrow with increased blasts. Cytogenetic analysis confirmed RUNX1::MECOM fusion. Furthermore, we discuss the molecular mechanisms underlying MECOM rearrangements, specifically the role of the EVI1 oncogene. AML associated with MECOM rearrangements is associated with poor prognosis and resistance to conventional therapies. While allogeneic hematopoietic stem cell transplantation (allo-HSCT) remains the only potential curative treatment, the high relapse rate limits its efficacy. Recent advancements in understanding the molecular drivers of MECOM-related AML suggest potential therapeutic strategies, including hypomethylating agents and novel combinations such as lenalidomide.Conclusion this case and literature review emphasizes the importance of long-term monitoring of cancer survivors treated with cytotoxic therapies, as well as awareness of rare translocations in MN-pCT.